BLACK POWER IN MAYA ANGELOU’S “STILL I RISE”, “PHENOMENAL WOMAN”, AND “WEEKEND GLORY” - Silvania Krisna; Liliek Soelistyo (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This article discusses the Black Power’s ideas inside the three poems of Maya Angelou, “Still I Rise”, “Phenomenal Woman”, and “Weekend Glory”. Maya Angelou was highly respected as a spokesperson for Blacks and women. The struggle of the author as a powerless Black woman can be seen from Angelou’s poems. This article tries to find out in what ways Black power is revealed in Maya Angelou’s three poems mentioned above. Moreover, Black power movement concept and figurative language are needed to reveal the idea of Black power in each poem. The analysis shows that there are differences of ideas of Black power in each poem. The Black power idea is the way to survive in the society, the way to express someone’s thought, and the ability to accept one’s identity as a Black woman. In the end, it can be concluded that the author is a powerful Black woman.